Chapter Da Vienna con amore: il caleidoscopio delle calligrafie settecentesche e il caso Orfelin - Lazarevic Di Giacomo, Persida (Biblioteca di Studi Slavistici, 2019)
This article examine handwriting textbooks from 18th-century Europe. In 1774 the court of Vienna charged Johann Ignaz Felbiger with reforming the schools and his book on penmanship (1775) became the standard reference for how to write. In 1776 the Court sought a book on penmanship to be used specifically in Serbian and Vlach schools; the textbook of Zaharija Orfelin (1778) came into being to fill this need. The textbooks of both Felbiger and Orphelin have their basis in Felbiger's first book on penmanship (1768). We also explore the possibility that other European handwriting manuals served as models for earlier works by Orfelin (1759, 1776).